Short-term resilience of Great Gray Owls to a megafire in California, USA. (29th January 2019) - Siegel, Rodney B; Eyes, Stephanie A; Tingley, Morgan W; Wu, Joanna X; Stock, Sarah L; Medley, Joseph R; Kalinowski, Ryan S; Casas, Angeles; Lima-Baumbach, Marcie; Rich, Adam C
ABSTRACT: Throughout western North America, longer, hotter fire seasons and dense fuels are yielding more frequent, larger, and higher-severity wildfires, including uncharacteristically large "megafires." Wildlife species associated with late-seral forest characteristics may be particularly vulnerable to habitat loss stemming from changing fire regimes. The Great Gray Owl ( Strix nebulosa ) is a state-listed endangered species in California that typically nests in large snags in well-shaded forests adjacent to montane meadows. The 2013 Rim Fire burned 104, 000 ha in Yosemite National Park and Stanislaus National Forest, making it the largest recorded fire in California's Sierra Nevada. The fire perimeter contained 23 meadows known to be occupied by Great Gray Owls during the decade prior to the fire, representing nearly a quarter of all known or suspected territories in California at the time. We analyzed 13 yr (2004–2016) of Great Gray Owl detection/non-detection data from 144 meadows in the central Sierra Nevada, including meadows inside and outside the Rim Fire perimeter in Yosemite National Park and on Stanislaus National Forest. During 3 yr of surveys after the fire, Great Gray Owls were detected at 21 of 22 meadows surveyed within the fire perimeter that were occupied during the decade prior to the fire. Bayesian hierarchical modeling revealed that, rather than decreasing after the fire, persistence of owls at meadows actually increased on both National Park Service (NPS) and non-NPS lands, while colonization rates exhibited no significant change. Within the burned area, these dynamics were unrelated to forest structure variables describing post-fire stands around individual meadows. Notably, post-fire increases in owl persistence occurred both inside and outside the fire perimeter, suggesting factors other than the fire were likely favorable to Great Gray Owls during the post-fire years. Great Gray Owls appear to have been largely resilient to effects of the Rim Fire during the 3 yr after it burned.